Evaluation Of Pesticide Use Towards The Implementation of Pollutant Release And Transfer Registers (PRTRs) In The Upper Citarum Watershed - Branden, Branden; Roosmini, Dwina (Jurnal Teknik Lingkungan, 2026)
Pollutant Release and Transfer Registers (PRTRs) are publicly based pollutant inventory systems that record the types, quantities, and sources of pollutant releases into the environment. This system promotes transparency and accountability in environmental management, enabling Indonesia to meet international environmental standards, including its accession process to the Organisation for Economic Co-operation and Development (OECD). This study aims to evaluate pesticide use in the Upper Citarum Watershed (DAS Citarum Hulu) as a foundation for implementing PRTRs in Indonesia. The research focuses on identifying the types, distribution, and usage patterns of pesticides in the agricultural sector; estimating pesticide emissions through runoff modelling; and analyzing the readiness of the water quality monitoring system. The methodology involves questionnaire surveys with farmers in West Bandung Regency, supported by secondary data such as rainfall, land area, and soil characteristics. Estimated pesticide residue concentrations are calculated based on factors such as precipitation, land slope, and soil organic carbon content. The findings of this study are expected to provide a foundation for strengthening Indonesia's environmental monitoring system and formulating national PRTRs policies. Additionally, the study highlights the importance of integrating data, public participation, and risk-based approaches in sustainable environmental management.